2002
DOI: 10.1046/j.1360-0443.2002.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Have we lost our way? The need for dynamic formulations of smoking relapse proneness

Abstract: Current smoking cessation treatments seem to differ from one another in the proportion of ex-smokers who survive the first few days of the quit attempt. After this initial effect, parallel relapse processes appear to unfold in all treatment groups; no available treatments seem to alter the nature of this late relapse process. True relapse prevention will require that we obtain a better understanding of the forces contributing to relapse across the span of the cessation attempt. A working model of dynamic relap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
168
1
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(181 citation statements)
references
References 59 publications
7
168
1
4
Order By: Relevance
“…For example, Piasecki, Fiore, McCarthy, and Baker (2002) theorized three sets of forces, namely, withdrawal, self-control, and the exhaustion of self-control, as co-determinants of relapse. These authors postulate that in an early period of a quit attempt, self-control is critical for preventing relapse, but later in the period, relapse is more under the influence of the residual strength of cue-specific factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Piasecki, Fiore, McCarthy, and Baker (2002) theorized three sets of forces, namely, withdrawal, self-control, and the exhaustion of self-control, as co-determinants of relapse. These authors postulate that in an early period of a quit attempt, self-control is critical for preventing relapse, but later in the period, relapse is more under the influence of the residual strength of cue-specific factors.…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested a more prominent role for the strength of urges to smoke on typical smoking days (Baker, Breslau, Covey, & Shiffman, 2012), but we do not know when might measuring this indicate a propensity to remain quit long term. If Piasecki et al (2002) are correct, then measures that focus on cue-specific cravings might provide useful information, in particular, cues that are associated with negative affect, as negative affect can be both a specific trigger and a reason for smoking (Borland, 2014). Residual beliefs about the value of smoking have also been associated with long-term relapse (Dijkstra & Borland, 2003).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Despite this increased attention to the dynamic nature of smoking cessation and attempts to hypothesize time-varying processes involved in smoking cessation (Piasecki et al, 2002), little is known about time-varying associations between smoking outcomes and their potential covariates (Shiyko, Lanza, Tan, Li, & Shiffman, 2012). For example, although smoking urges and negative affect have been shown to predict smoking lapse after a quit attempt (Berkman, Dickenson, Falk, & Lieberman, 2011;Shiffman & Waters, 2004), it is not known whether these factors play a stronger role in smoking lapse during certain periods.…”
mentioning
confidence: 99%
“…Smoking cessation therapies, such as pharmacotherapy or counseling, can more than double abstinence rates, but even with such aids, only 15%-30% of individuals are successful in a given quit attempt (Fiore, Bailey, & Cohen, 2000). Piasecki, Fiore, McCarthy, and Baker (2002) have suggested that this lack of treatment success may result from a poor understanding of addiction processes and that basic research on smoking and cessation dynamics is essential.…”
mentioning
confidence: 99%
“…In addition, many studies do not separate out those smokers who lapsed and then returned to abstinence from those who lapsed and then reverted to regular smoking (i.e., relapsed). Thus, long-term abstinence, as it has been measured, may be an insensitive outcome by which to measure relations between cessation treatments and cessation processes (Piasecki et al, 2002;Piasecki, 2006;Shiffman et al, 2006). …”
mentioning
confidence: 99%